Erectile dysfunction predictors in hypertensives at a primary care clinic in Southern Nigeria - Oluwagbenga Ogunfowokan; Sylvia I. Ezemenahi; Anthonia N. Alabi; Adesuwa Q. Aigbokhaode; Bamidele A. Ogunfowokan (AOSIS, 2022)
Background: Erectile dysfunction (ED) has been described as an important public health problem by the National Institutes of Health Consensus Development Conference Panel. It causes significant distress in men and dysfunctional family dynamics. Aim: This study sought to identify the relationship between level of education and ED amongst hypertensive men (aged 30-89 years) attending outpatient clinics (OPCs) at the Federal Medical Centre (FMC), Asaba. Setting: This study was conducted in the OPCs at FMC, Asaba, Delta State, Nigeria. Methods: After obtaining approval from the ethics and research committees in Asaba, 184 consenting hypertensive men who met the eligibility criteria were selected by systematic random sampling to participate in the study from October 2015 to January 2016. This study was a cross-sectional survey. Data were collected with a semistructured, interviewer-administered questionnaire adopted from the International Index of Sexual Health Inventory for Men. The study complied with the principles of Helsinki and Good Clinical Practice. Results: The mean age ± standard deviation and range of the respondents were 55.1 (±12.4) and 30-89 years, respectively. On logistic regression, higher level of education (secondary school and above) (odds ratio [OR] = 15.943, 95% confidence interval [CI] = 1.517-167.502) was found to be a predictor of ED amongst the study participants. Conclusion: This study showed that formal education up to secondary level and use of diuretics were significantly associated with ED amongst adults with hypertension.